A propósito do novo código de processo civil brasileiro / About the New Brazilian Civil Procedure Code - Atienza, Manuel (2017)
ResumoO presente trabalho reflete sobre os sistemas tradicionais de criação judicial do direito e insere as súmulas brasileiras como um terceiro procedimento e as respectivas implicações. Aborda a maneira como o novo Código de Processo Civil brasileiro trata a tensão entre a certeza (a estabilidade) e a justiça (a coerência) e as interpretações fornecidas pela doutrina. Ao fim, aponta o que é verdadeiramente importante para o bom funcionamento do sistema: a obrigação de motivação adequada das decisões por parte dos órgãos públicos.Palavras-chaves: Precedentes. Súmulas. Novo Código de Processo Civil.AbstractThe present work reflects on traditional systems of judicial creation of law, and incorporates the Brazilian precedents system (súmulas) as a third kind of procedure and the resulting implications of this. It addresses how the new Brazilian Code of Civil Procedure deals with the tension between certainty (stability) and justice (coherence) and the interpretations that doctrine provides. Finally, it points out what is really important for the proper functioning of the system: the obligation for public bodies to adequately justify their decisions.Keywords: Precedents. Súmulas. New Brazilian Code of Civil Procedure.